(untitled) (KASBIT Business Journal, 2021)
The core purpose of this study is to revisit the trust of online consumers towards e-retailers in Pakistan. However, numerous studies have highlighted those factors which are related to online business rather than human behavior. Although, the study is based on a quantitative research technique and used a deductive approach. Moreover, the survey strategy chose to collect data. The close-ended questionnaire was distributed among “300” respondents through a large portion of respondents from the main city “Karachi” with the help of “purposive sampling” and followed a cross-sectional pattern. The collected data were evaluated in the smart PLS and executed “structural equation modeling (SEM)” to analyze data. Besides this, the gathered data were quite reliable and valid, and also were not found multicollinearity issues. Furthermore, two indirect relationships and three direct relationships have been found significant. Also, some important limitations have been underlined like the study used a small sample size of 300. Secondly, because of time constraints, a cross-sectional time horizon was followed. Though, a larger portion of data was collected from the main city. Last, the study has some contributions such as introducing a new conceptual model, highlights essential areas to improve consumer’s online trust.